Out-of-school-time STEM programs for females : implications for research and practice. volume I, - Wiest, Lynda R.; Sanchez, Jafeth E.; Crawford-Ferre, Heather Glynn (Emerald Publishing Limited, 2017)
Science, technology, engineering, and mathematics (STEM) disciplines play a pivotal role in societal progress and economic prosperity, in addition to enhancing individual lives. However, U.S. students lack strong STEM performance in an international context. The pool of STEM-proficient workers is thus insufficient to fuel the nation, with females being one group that is noticeably absent.Out-of-school-time (OST) programs, which are on the rise, are increasingly suggested as a way to support and encourage females in STEM. Data collected from participants in OST programs have shown improved achievement, interest, and confidence in STEM, as well as greater awareness of STEM role models and careers.Out-of-School-Time STEM Programs for Females: Implications for Research and Practice features seven OST STEM programs for females from across the United States that run one week to one year in length. In this book, the chapter authors describe their programs, the effectiveness of those programs, and practical implications of their program evaluation data. This book is the first of its kind to offer researchers, educators, school administrators, policy makers, and others detailed insight into the promise and practice of out-of-school-time STEM programs for females.
Includes index.
Keywords: Women in science -- United States.; Girls -- Education -- United States.; Minorities in science -- United States.; Science -- Study and teaching -- United States.; Technology -- Study and teaching -- United States.; Engineering -- Study and teaching -- United States.; Mathematics -- Study and teaching -- United States.; Education -- Teaching -- Subjects -- Science & Technology.; Extra-curricular activities.; Teaching of a specific subject.; Educational: Sciences, general science.; elektronické knihy; electronic books